Mechanical and wear properties of aluminum coating prepared by cold spraying - Yusuf, NA; Afandi, NF; Salim, MA; Misran, H; Omar, Nooririnah (Universiti Putra Malaysia, 2014)
In this study, Al powders were deposited onto Al substrates using cold spray to form a coating. The main objective is to investigate and compare the microstructure, mechanical and wear properties of Al coating to that of the Al substrate. The microstructure of the coating and substrate were observed using Scanning electron microscope (SEM),hardness was evaluated using Vickers hardness test and wear properties were investigated using a pin on disc wear test machine.